Effects of Consumer Involvement, Consumer Knowledge, and Consumer Education on Decision Quality and Consumer Loyalty in Cosmetics Industry - Han, Ching-Cheng (2008)
This study examines the effects of consumer education, consumer knowledge, and consumer involvement on decision quality and consumer loyalty. First, the research gives an overview of the industrial background and literature review. In addition, the relationships between each construct are indicated based on the pervious researches. A quantitative research in the form of online questionnaire was conducted and results are analysed. Finally, the conclusion and limitation of the study is reported. Total 128 effective questionnaires were collected in this research. The results showed that consumer knowledge and consumer involvement have a positive relationship with decision quality, while decision quality is positively associated with consumer loyalty. However, consumer education has no influence on decision quality or consumer loyalty. Besides, the there are no moderating impact from consumer knowledge and consumer involvement in cosmetics industry. The recommendation for effects of consumer education is to provide a useful skill or information for consumers. Although consumer education showed little influence in cosmetics industry, it still provides some value for both theoretical domain and practical environment.